Organizational foundations of preparation and selection of athletes - Oksana Shynkaruk (Kharkiv State Academy of Physical Culture, 2016)
Purpose: to determine organizational conditions for the preparation and selection of a remote reserve in modern conditions of development of sports. Material & Methods: method of research - analysis of scientific-methodical literature, documentary t regulatory documents and Internet data, systematization and generalization, observation. Results: the article considers the problem of selection, orientation and training of athletes in the course of many years improvement, the location of the system children and youth and reserve sports in the process. Identifies three levels of training, selection and orientation of athletes: distant and the nearest reserve of national teams on sports. Conclusions: the efficiency of preparation of sportsmen depend on creating organizational conditions that are based on a rational distribution of material and technical, financial, personnel, scientific-methodical and medical support at all levels of training athletes.